The impact of touchy topics on vague language use - Zhang, Grace (John Benjamins Publishing Company, 2013)
Vague language (VL), an integral part of language, has been attracting increased attention in linguistic studies. VL is a versatile tool of communication in presenting the world as an imprecise but powerful manner. This study explores on overlooked issue: the relationship between the sensitivity of topics and the use of VL, particularly between topical sensitivity and the form and function of VL items. The corpus consists of semi-controlled spoken interactions between Western Australian tertiary students who were asked to converse on two topics: asylum seekers (touchy) and weekend activities (less touchy). The findings reveal the impact of sensitivity, manifested by different VL frequencies (macro level) and forms (micro level) used in the different topics. More VL, and particular forms VL (e.g. I think, some, or something), were used in the asylum seeker discourse. As the level of topical sensitivity increases, the level of vagueness in talk-in-interactions also increases: that is, the level of sensitivity, VL frequency and specific VL items are positively related. Showing how participants use VL in responding to different degrees of sensitivity, this study enriches the scare literature by providing fresh insights and new resources in this important research area. It is expected that the impact of touchy topics may be applicable to other areas of linguistic studies.